(untitled) (Texas Journal of Philology, Culture and History, 2024)
This article is considering the combination of fantastic and realistic categories in modern English children’s literature, in particular in Joanne Rowling’s novel about Harry Potter. The article shows that realistic elements, such as toponyms, zoonyms, phytonyms, people, physics, natural phenomena and laws of nature in fantasy works bring the world of fantasy closer to the real world and, as a result, lead to mutual understanding, harmony of realistic and fantastic elements